Characterization of the anamorphic and spatial frequency dependent phenomenon in liquid crystal on silicon displays - Lobato, L. (2011)
The diffractive efficiency of Liquid Crystal on Silicon (LCoS) displays can be greatly diminished by the appearance of temporal phase fluctuations in the reflected beam, depolarization effects and also because of phase modulation depths smaller than 2π. In order to maximize the efficiency of the Diffractive Optical Elements (DOEs) implemented in the LCoS device, the Minimum Euclidean Distance principle can be applied. However, not all the diffractive elements can be corrected in the same way due to the anamorphic and spatial frequency dependent phenomenon, which is related to the LCoS response, largely depending on the period and the spatial orientation of the generated DOE. Experimental evidence for the anamorphic and spatial frequency dependent phenomenon is provided in this paper, as well as a comparative study between the LCoS display response for binary gratings of different periods.